Freedom, self-interest and the urban: From political to post-political economy - Jackson, Mark (Interstices: Journal of Architecture and Related Arts, 2015)
The global financial crash of 2008 had many precipitating causes and has had massive repercussions over the past seven years on global economic activity as well as on how urban infrastructure, housing and services are financed and delivered. The crash was precipitated by the massive escalation in global derivatives trading, especially that related to low income housing mortgages. It was also precipitated by a failure of predictive measures, probability models and the calculability of market forecasts that have been the foundation to economic planning since the emergence of political economy at the end of the eighteenth century. This paper aims to do two things in relation to this recent episode in economic history. The first is to undertake a genealogy of the emergence of political economy and a State’s reliance on probability and statistics for its governance. This is primarily analysed through the writings of Michel Foucault on space, power and the aleatory. The second is to introduce the thinking of the economics philosopher, Elie Ayache, who wrote a book after the crash on the end of probability. The paper’s overall aim is to bring the work of Foucault and Ayache together in drawing out a radical thinking with respect to the urban of the relation between space, power, contingency, and writing.